Energy efficiency and emissions of CO2, CH4, and N2O in organic and conventional rice production - Guareschi, Roni Fernandes; Martins, Marcio dos Reis; Urquiaga, Segundo; Alves, Bruno José Rodrigues; Boddey, Robert Michael; Sarkis, Leonardo Fernandes (Semina: Ciências Agrárias, 2020)
Rice is the second-most produced cereal worldwide and actively contributes to greenhouse gas (GHG) emissions, particularly methane, especially under deepwater production. Assessments of energy efficiency (EE) and GHG emissions can indicate the sustainability level of agrosystems and support decisions related to the reduction of production costs and environmental pollution. This study aimed to assess both EE and GHG emissions in organic and conventional rice production in the Southern region of Brazil. For this study, eight rice fields were evaluated. Energy inputs and outputs were calculated by multiplying the production input amounts by their respective calorific values or energy coefficients at each stage of production. EE was determined using the ratio between the total energy output and the total energy consumed during the production process. GHG emissions were estimated using the principles of the lifecycle assessment methodology in addition to the Intergovernmental Panel on Climate Change (IPCC) recommendations. Each 1.0 MJ consumed during the production of organic and conventional rice produced renewable energy averages of 10.5 MJ and 7.90 MJ, respectively, as grains. The primary energy expenses for organic rice were represented by seeds, fuel, tractors, and agricultural machinery and implements, and those for conventional rice were seeds, fuel, and fertilizers. Each kilogram of organic and conventional rice produced accounted for the emission of 0.21 and 0.32 kg of CO2eq, respectively, during the production cycles and delivery to the warehouse, with seeds, fuel, and fertilizers being the main sources of CO2eq emissions to the atmosphere.